Meditation modalities for ADHD in minority pediatric populations in the USA: a scoping review - Shahrzad Bazargan-Hejazi; Christopher Martin; Bellamy Hall; Jeneane Hamideh; Miranda Lam; Antonia Osuna-Garcia; Darlene Parker-Kelly; Derek O. Pipolo; Myra Usmani; Stacey A. Teruya (Tabriz University of Medical Sciences, 2024)
Background: Roughly 10% of children aged 3 -17 in the USA are diagnosed with attention-deficit hyperactivity disorder (ADHD), and minorities are less likely to initiate common pharmacologic treatment. We conducted a review of the literature to examine meditation as a safe, effective, and low-cost alternative. Methods: We searched PubMed and other journals using "meditation," "mindfulness," "minority," related keywords, and relevant MeSH terms. Eligible studies involved racial/ethnic minorities in the USA, reported quantitative psychosocial outcomes, and were published in a peer-reviewed, English-language journal. Results: Out of 119 "hits," 111 were eliminated as duplicates or were not relevant. A full-text review of the remaining eight revealed that none fully met our eligibility criteria. Besides the obvious lack of studies, those reviewed reported incomplete demographic and clinical data. They also employed different and inconsistent research methodologies, interventions and modalities, and statistical analyses. This hindered understanding exactly which populations may benefit from meditation, and for which specific symptoms. Conclusion: We recommend a socio-ecological model in examining intervention modalities, especially in the context of intrapersonal, interpersonal, organizational, environmental, and policy domains. We also suggest the possible inclusion of research older than 10 years, conducted outside of the USA, on minority and non-minority populations, for supplementary and confirmatory data. We advocate for consistency in study design and data collection, which would help align research conducted in different countries. Searches should also include variations of meditation such as "mindfulness" and "guided imagery," and associated symptoms and comorbidities of ADHD, including "learning disorder" and "behavioral problems."